Gaya Kepemimpinan Adaptif untuk Generasi Milenial - Kasmanto Kasmanto; Adams Desto Edison Nasseri; Yani Restiani Widjaja; Purwadhi Purwadhi (STIKes Ibnu Sina Ajibarang, 2024)
Leaders can influence individuals or groups to achieve goals. If most of the employees' needs are not met, managers must be able to adjust their leadership style and know how to identify and adapt to changes in employees' needs. Otherwise, employees will not have good prospects in the organizational world. Millennial leaders, who are mostly members of an organization or team, are driven by the millennial generation and face more complex challenges. Because they value freedom, flexibility, open communication, supervisors and colleagues, and the use of technology, millennials are more difficult to retain within a company. The aim of this research is to determine whether adaptive leadership styles are effective in managing the current millennial generation. This study is qualitative and uses data analysis methods in a literature review. The goal is to discover and examine effective leadership styles and techniques for millennials. The results indicate that adaptive leadership approaches are beneficial as they help individuals overcome difficulties and adapt to changes. However, adaptive management theory also has its weaknesses. For instance, it is unclear how the key components of the adaptation process work and how these relationships support the adaptation process. According to Rainer Turangan (2015), a good leader should be able to adapt to uncertain future conditions, work across countries and cultures, and create a creative environment.